Protocolo PROCISUR de verificación y validación de soluciones digitales Agtech - Calderon Diaz, Facundo Javier; Tallarico, Gabriela Adriana; Mondo, Vitor Henrique Vaz; Best, Stanley; Carrillo, Hugo; Tiscornia, Guadalupe (IICA (Uruguay), 2025)
También disponible en portugués